2022
DOI: 10.1021/acsptsci.1c00270
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Therapeutic Peptide for Cachexia Suggests a Platform Approach for Drug-like Peptides

Abstract: During the development of a melanocortin (MC) peptide drug to treat the condition of cachexia (a hypermetabolic state producing lean body mass wasting), we were confronted with the need for peptide transport across the blood–brain barrier (BBB): the MC-4 receptors (MC4Rs) for metabolic rate control are located in the hypothalamus, i.e., behind the BBB. Using the term “peptides with BBB transport”, we screened the medical literature like a peptide library. This revealed numerous “hits”peptides with BBB transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…72,78 We tested the effect of several peripherally administered peptides described here, including PG-934, SBL-MC-31, SBL-MC-69, SBL-MC-93, and SBL-MC-94 on food intake (data not shown). Despite featuring the previously described favorable Pro 6 , shown to stabilize the macrocyclic ring in solution, 79 none of the assayed peptides affected food intake when administered by the intraperitoneal route.…”
Section: Distinctive Antagonist Potency and Selectivity Profiles Dist...mentioning
confidence: 75%
See 1 more Smart Citation
“…72,78 We tested the effect of several peripherally administered peptides described here, including PG-934, SBL-MC-31, SBL-MC-69, SBL-MC-93, and SBL-MC-94 on food intake (data not shown). Despite featuring the previously described favorable Pro 6 , shown to stabilize the macrocyclic ring in solution, 79 none of the assayed peptides affected food intake when administered by the intraperitoneal route.…”
Section: Distinctive Antagonist Potency and Selectivity Profiles Dist...mentioning
confidence: 75%
“…As reported by others, SHU9119 only affected food intake when administered centrally, although some SHU9119 -derived peptides such as PG-932 and TCMCB07 show activity when administered peripherally. , We tested the effect of several peripherally administered peptides described here, including PG-934 , SBL-MC-31 , SBL-MC-69 , SBL-MC-93 , and SBL-MC-94 on food intake (data not shown). Despite featuring the previously described favorable Pro 6 , shown to stabilize the macrocyclic ring in solution, none of the assayed peptides affected food intake when administered by the intraperitoneal route.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this study, we cloned canine MC3R and investigated its pharmacological properties. We have reported cMC4R pharmacology previously [ 54 , 61 ]. In the current study, we also identified a MRAP2 variant, MRAP2b .…”
Section: Discussionmentioning
confidence: 99%
“…TCMCB07, with the structure Ac‐Nle‐cyclo[Asp‐Pro‐DNal(2′)‐Arg‐Trp‐Lys]‐DVal‐DPro‐NH 2 , is a cyclic substituted melanocortin antagonist 13 which successfully treats cachexia in rodent models of cachexia 14 . The MCR4 in dogs is fully functional, 15 and TCMCB07 is a potent antagonist at the rat, human, and canine MC3 and MC4 receptors in terms of receptor binding and antagonism of cAMP activation by the α‐MSH analogue [Nle 4 , DPhe 7 ]‐MSH (NDP‐MSH; Melanotan‐Ι) 16 . In addition, the pharmacokinetics and safety of TCMCB07 in normal beagle dogs are established 11 .…”
Section: Introductionmentioning
confidence: 99%
“…14 The MCR4 in dogs is fully functional, 15 and TCMCB07 is a potent antagonist at the rat, human, and canine MC3 and MC4 receptors in terms of receptor binding and antagonism of cAMP activation by the α-MSH analogue [Nle 4 , DPhe 7 ]-MSH (NDP-MSH; Melanotan-Ι). 16 In addition, the pharmacokinetics and safety of TCMCB07 in normal beagle dogs are established. 11 However, further studies are necessary to expand our knowledge of TCMCB07 in a real-world model of naturally occurring disease.…”
Section: Introductionmentioning
confidence: 99%